Optimizing dynamic range of magnetorheological fluid dampers: modeling and simulation - Kasemi, Banna; Abdul Muthalif, Asan Gani; Rashid, Muhammad Mahbubur; Rahman, Mahmudur (2011)
The viscosity of Magnetorheological (MR) fluids changes dramatically in the presence of an electric or magnetic field, leading to their being referred to as ‘smart fluids’. These fluids have important applications in the field of damping systems. The MR damper parameters are different for different application and there always exist a trade-off. The optimal values of the parameters are important in the design of MR damper for a particular application. Dynamic range is one of the key parameters of the MR fluid damper. This study presents the mathematical derivation of optimal yield stress and shear force to determine the optimal dynamic range of an MR fluid damper.